
#1
Oct311, 08:01 AM

P: 153

1. The problem statement, all variables and given/known data
(a) Give a resolution refutation of the following formula: (x ∨ y) ∧ (y ∨ ¬z ∨ ¬x) ∧ ¬x ∧ (¬y ∨ x) (b) Convert the formula into CNF and give a resolution refutation for it: x_{1} ∧ (x_{1} ↔ x_{2}) ∧ (x_{2} ↔ x_{3}) ∧ (x_{3} →¬ x_{1}) 2. Relevant equations n/a 3. The attempt at a solution I need help with basic Resolution Refutation. If someone could walk me through it, or give an easier explanation then the one my prof tried to give that would be greatly appreciated 


Register to reply 
Related Discussions  
The Refutation of Bohmian Mechanics  Quantum Physics  235  
Kalam cosmological argument & Refutation  General Discussion  5  
Refutation of reductionism (excerpt from "The Fabric of Reality," by David Deutsch)  General Discussion  24 